Distortion or Clarification: Defining Highly Qualified Teachers and the Relationship between Certification and Achievement - Jacob M Marszalek; Arthur L Odom; Steven M. LaNasa; Susan A. Adler (Arizona State University, 2010)
Recent studies of the relationship between teacher preparation pathways and student achievement have resulted in similar statistics but contradictory conclusions. These studies as a group have several limits: they sometimes focus on student-level indicators when many policy decisions are made with indicators at the school-level or above, are limited to specific urban locations or grade levels, or neglect the potential influence of building type, as defined as the grade-levels serviced. Using statewide data from the 2004-2005 school year, we examined the relationships between school-level indicators of student achievement on nationally-normed tests and proportions of alternatively certified teachers, while controlling for building type and other relevant covariates. Our findings indicate that the relationship between teacher preparation and student achievement at the school level depends on whether the building mixes multiple grade levels (e.g., elementary and middle). The implications of Missouri's policy change for research and school improvement are discussed with respect to the current high-stakes testing environment.